Pengaruh Kompetensi Pedagogik, Kepribadian Sosial, dan Profesional Terhadap Peningkatan Kinerja - endah dwi yuniarti (JMK (Jurnal Manajemen dan Kewirausahaan), 2017)
The WOW SHORT BTPN agents selected from the clients trusted SHORT BTPN and memenui criteria and requirements. Based on observations made by researchers, HR appointed as agents have less competence, personality, Social Pedagogy, and professional. Because in the Pedagogic competence, in practice less agents understand the work system in serving the customer's transactions.Based on the results of analysis and hypothesis testing that has been done, then the conclusion can be drawn as follows: 1) pedagogic Competence (X1), personality (X2), social (X3) and professional (X4) influential partially against the performance of agents direct and positive WOW SHORT BTPN.; 2) pedagogic competencies together (X1), personality (X2) competence, social competence (X3) and professional competence (X4) simultaneous effect on performance agent (Y) SHORT BTPN WOW on SHORT BTPN Kediri Branch Office.